Síntese, caracterização e estrutura molecular de complexos de coordenação de cobre(II) com ligantes derivados de 1,3,4-tiadiazóis - Londero, Ana Júlia Zimmermann (2024)
This work presents the synthesis and characterization of five novel ligands derived from 1,3,4-thiadiazoles and thirteen new coordination compounds using copper(II) salts. The compounds are divided into three main blocks. The first block addresses the complexes with symmetrical ligands derived from the precursor 2,6-pyridinedicarbonyl dichloride. The ligand N,N’-bis(1,3,4-thiadiazol-2-thione)-2,6-pyridinedicarboxamide (H4L1) exhibited low solubility but was still reactive toward Cu²⁺ ions, forming the insoluble polymeric compound [Cu3(μ-Cl)2(H2L1)2]n (1). The lack of solubility of compound (1) led to the preparation of the ligand N,N’-bis(5-(methylthio)-1,3,4-thiadiazol-2-yl)-2,6-pyridinedicarboxamide (H2L2), in which a methyl group was incorporated into the thione of the 1,3,4-thiadiazole rings. This ligand allowed the formation of two Cu²⁺ compounds depending on the order of addition of the base (triethylamine): [Cu2(μ-OH2)(L2)2] (2) and [Cu5(dmf)(μ3-OH)2(L2)3(L2b)] (3). The second block consists of the preparation of an asymmetric ligand, ethyl-6-((5-(methylthio)-1,3,4-thiadiazol-2-yl)carbamoyl)picolinate (HL3), derived from the precursor 6-propionylpicolinamide chloride, which was prepared beforehand. This molecule showed greater solubility due to the aliphatic group. The formation of copper(I/II) and copper(II) complexes was influenced by the solvents, the order of addition of triethylamine, and the anion of the salt, highlighting the rare example of a Cu+/Cu2+ complex [Cu2(μ-Cl)(L3)2] (4), which has a delocalized electron between the two copper centers. When the base is added after the ligand, the hydrolysis product is observed [Cu(H2O)2(L3b)] (5), and when the copper(II) salt is replaced with acetate, the complex [Cu2(μ-CH3COO)2(L3)2] (6) is formed. The third block explores ligands derived from picolinamide chloride and 4-fluorobenzamide chloride: N-(5-(methylthio)-1,3,4-thiadiazol-2-yl)picolinamide (HL4) and 4-fluoro-N-(5-(methylthio)-1,3,4-thiadiazol-2-yl)benzamide (HL5). Three new coordination compounds were obtained from HL4: [Cu2(μ-Cl)2(L4)2] (7) and [Cu2(μ-CH3COO)2(L4)2] (8), dependent on the nature of the metal salt, as well as the complex [Cu(H2O)Cl2(HL4)] (9), which was explored regarding the use of acidic medium in its formation. The ligand HL5, containing the 4-fluorobenzoyl group, exhibited distinct chelating behavior compared to the other ligands, coordinating through the oxygen atom of the amide group along with a nitrogen atom from the thiadiazole ring, leading to the formation of the compound [Cu(L5)2] (10), which is independent of the counterion of the salt used. The reaction of HL5 with CuCl2 in neutral or acidic medium led to the formation of [Cu(MeOH)2Cl2(HL5)2] (11), for which it was observed that, with prolonged storage or heating, the coordinated methanol molecules were lost, generating the complex [CuCl2(HL5)2] (11b). The molecular structures of the ligands and complexes were obtained by X-ray diffraction of single crystals (with some exceptions, for which structures were suggested). In the solid state, the compounds were characterized by powder X-ray diffraction, infrared spectroscopy, Raman spectroscopy, and diffuse reflectance, as well as elemental analysis. Soluble compounds were characterized by spectroscopy in the ultraviolet-visible region, electron paramagnetic resonance (complexes), and nuclear magnetic resonance (ligands). The compounds for which single crystals could not be obtained were also characterized using the combined techniques of scanning electron microscopy and energy dispersive spectroscopy to verify their chemical composition. Calculations using density functional theory were performed to understand the cis-O∙∙∙S conformation present in the compounds. Assays against mycobacteria were conducted on the soluble samples; however, no appreciable minimum inhibitory concentration results were observed against the tested strains, whereas the anticancer activity tests revealed promising compounds, such as HL3 and 9, with high selectivity for MCF7 tumor cells.